Traverse Grinding of X6CrNiMoTi Steel and its Final Surface Quality for Giving Cutting Conditions - Nataša Náprstková; Martin Novák; Júlia Hricová (Production Engineering Archives, 2015)
Machining of stainless steels is often an important used technology. Products made from these materials are often used in mechan-ical engineering and the quality of workpiece surface roughness after machining respective grinding is one of the important parameters that illustrates the quality of the machining process. This paper deals with the influence of cutting conditions when grinding steel X6CrNiMoTi (EN ISO) on the machined quality surface (roughness, circularity). Grinding of samples was carried out by feed grinding and the measured values were analyzed. On the machined samples parameters were all monitored and measured in the laboratory of precision measurements at the Faculty of Production Technology and Management of Jan Evangelista Purkyně University in Ústí nad Labem and the devices Hommel tester T1000 and Hommel tester Form 1000 were used. Measuring was done according to ČSN EN ISO 4287.